Guarantee of due process hearing: human right violated to the importer in the customs procedure - Aguado Romero, Gabriela (DIXI, 2019)
Purpose: The purpose of this study is to make an analysis about the human right called guarantee of due process hearing, recognized in the Political Constitution of the United Mexican States and in the International Law of Human Rights. We can see that nowadays this human right is violated in the customs department, within the second legislation. This violation happens when the principle of legality is ignored, granting a margin of discretion in favor of the customs authority against the importer.Methods: for the development of this study, an exegetical methodology and the use of the bibliographic documentary technique will be used.Results: Analyzing this situation, we can observe there is a lack of harmonization to protect human rights, despite the fact that the constitutional reform of 2011 in the field of human right, brings a different way to interpret ate the Constitution and the international treaties in which Mexico is involved, it is obvious that the legislation on customs matters in Mexico, still has sections that transgress, among others, the guarantee of due process hearing.Conclusions: State fails to comply with the obligation to respect, protect, promote and guarantee the enforcement and enjoyment of the human rights and fundamental freedoms of citizens who are within its jurisdiction.
Keywords: customs; constitution; human rights; international law; guarantee of due process hearing